PENGARUH PENGETAHUAN AUDITOR, PENGALAMAN AUDITOR, KOMPLEKSITAS TUGAS, LOCUS OF CONTROL, DAN TEKANAN KETAATAN TERHADAP AUDIT JUDGMENT (Studi Kasus Pada Perwakilan BPKP Provinsi Riau) - Febrina Prima Putri; Kennedy -; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This Research aimed to examine the effect of Auditor Knowledge, Experience Auditor, Task Complexity, Locus Of Control, and Pressure Obedience On Audit Judgment. This research was conducted at BPKP of Pekanbaru City. Thepopulation of this research were auditor who worked in BPKP of Pekanbaru City.The sampling method used in this study is purposive sampling method. The sample used in this research were 92 respondents. The data usage in this research was primary data collecting through the questionnaires. The questionaires processed were totals as many as 50 questionnaires from 100 questionnaires diffused. According to the data quality consisted of the validity test, reliability test, and normality test indicated that all variables could be valid, reliable, and normal so that for the next, the items of every variable concept was appropriately use as an indicator. The result of this research indicated that the auditor knowledge, locus of control, and pressure obedience have influence to audit judgment. Whilst the experience auditor, and task complexity don’t have influence to audit judgment.Keywords: Audit Judgment, Locus Of Control, Audit Knowledge, Experience Auditor, and Task Complexity